Low‐temperature sintering and thermal stability of Li2GeO3‐based microwave dielectric ceramics with low permittivity. Issue 10 (30th April 2018) - Yin, Changzhi; Xiang, Huaicheng; Li, Chunchun; Porwal, Harshit; Fang, Liang
Abstract: A low‐permittivity dielectric ceramic Li2 GeO3 was prepared by the solid‐state reaction route. Single‐phase Li2 GeO3 crystallized in an orthorhombic structure. Dense ceramics with high relative density and homogeneous microstructure were obtained as sintered at 1000‐1100°C. The optimum microwave dielectric properties were achieved in the sample sintered at 1080°C with a high relative density 96%, a relative permittivity ε r 6.36, a quality factor Q × f 29 000 GHz (at 14.5 GHz), and a temperature coefficient of resonance frequency τ f −72 ppm/ ° C. The sintering temperature of Li2 GeO3 was successfully lowered via the appropriate addition of B2 O3 . Only 2 wt.% B2 O3 addition contributed to a 21.2% decrease in sintering temperature to 850°C without deteriorating the dielectric properties. The temperature dependence of the resonance frequency was successfully suppressed by the addition of TiO2 to form Li2 TiO3 with a positive τ f value. These results demonstrate potential applications of Li2 GeO3 in low‐temperature cofiring ceramics technology.